Identitas Budaya dalam Novel Lusifer Lusifer karya Venerdi Handoyo: Kajian Postmodernisme Jean Francois Lyotard - Saputra, Yusril; Satriani, Irma (Fakultas Sastra Universitas Muslim Indonesia, 2025)
This study explores cultural identity in the novel Lusifer Lusifer by Venerdi Handoyo using Jean Francois Lyotard postmodernism approach. Concentrating on the representation of cultural identity in the form of religion, identity deception and masking, cultural adoption, and forms of irony. concentrating on irony in the text, religious representation, identity deception, and cultural adoption. The novel Lusifer Lusifer by Venerdi Handoyo shows how elements of Christian culture influence the daily lives of its characters through family relationships, religious rituals, and spiritual symbols. In this novel, postmodernism is depicted through the perspective that modernism does not meet the needs of humans as a whole and that religion is part of a collective identity, not just a personal belief. The results show that it offers a reflection on the relationship between religion, culture, and identity and criticizes the norms of modern society. The symbols used and adapted by the characters in this work form a cultural identity, depicting the conflict between the influence of modern culture and religious beliefs.